evolution and ecology of floral morphology in Aquilegia and the influence of horticulture on its emergence as a model system - Hodges, S. A (Acta horticulturae, 2015)
The columbine genus Aquilegia has been grown as a garden ornamental for centuries. Because of its unusual floral shape with the sepals being petaloid and colorful and the petals forming slender nectar spurs, many collections were made and species have been available to scientists as well as horticulturalists. Given its widespread natural distribution throughout the northern hemisphere, this availability was essential for early studies establishing that species in the genus were often highly intercompatible and their hybrids could be established. This led to a number of studies showing the relatively simple genetic inheritance of many of the dramatic differences among flowers of various species. More recent work has established the phylogenetic relationships among most of the species and showing that the genus had a burst of diversification after evolving the distinctive nectar spurs. Other studies have shown that this burst of diversification was likely due to adaptation to different pollinators, especially in North America, with changes in flower color, orientation and spur length to match the preferences and tongue lengths of new pollinators. Further studies have dissected the genetic basis of some of these traits. Aquilegia has also been noteworthy for its contributions to our understanding of the evolution of floral organ identity and horticultural varieties have, and will continue, to aid in these efforts. Aquilegia has now been the subject of substantial effort to develop it as a new model genomic system with the establishment of a high-quality reference sequence, derived from a highly inbred horticultural line as well as other resources such as a functional assay to assess specific gene functions. These resources poise Aquilegia to continue to be at the forefront of plant evolutionary and ecological research.